Digital-Game-Based Language Learning for Children: A Study in Vocabulary - Chandra Chandra; Catur Kepirianto (Department of Linguistics, Faculty of Humanities, Diponegoro University, 2021)
In modern age, people can learn or acquire a second language with the help of technology. The development of technology allows people to create an application called Digital-Based Language Learning (DGBLL). An example of a game application used during research is Studycat’s “Fun English”. This thesis discusses the useof DGBLL in the learning of English vocabulary as a second language. This research is aimed to identify phonemes that are difficult to be pronounced by Indonesian children, to identify the supporting factors for second language acquisition, and to compare the results of before and after the use of DGBLL in children.The writer uses the purposive sampling method, participant observation or referred as the Simak Bebas Libat Cakap technique, and recording technique in collecting data. The recorded data will be analyzed in contrastive analysis method to investigate which phonemes are difficult for children to pronounce.There are three findings of the research. First, the findings show most of the children as subjects find it hard to pronouncethe phonemes [ʤ]; [ʈʃ]; [ð]; [θ]; [æ]; [ʌ]. Second, the findings show that an essential part a second language learning is motivation to learn the language. Third, DGBLL is a useful tool to improve the subjects’ English vocabulary.Keywords: DGBLL; second language acquisition; contrasitive analysis